Probing cytoskeletal pre-stress and nuclear mechanics in endothelial cells with spatiotemporally controlled (de-)adhesion kinetics on micropatterned substrates - Versaevel, Marie (Cell Adh Migr, 2016)
The mechanical properties of living cells reflect their propensity to migrate and respond to external forces. Both cellular and nuclear stiffnesses are strongly influenced by the rigidity of the extracellular matrix (ECM) through reorganization of the cyto- and nucleoskeletal protein connections. Changes in this architectural continuum affect cell mechanics and underlie many pathological conditions. In this context, an accurate and combined quantification of the mechanical properties of both cells and nuclei can contribute to a better understanding of cellular (dys-)function. To address this challenge, we have established a robust method for probing cellular and nuclear deformation during spreading and detachment from micropatterned substrates. We show that (de-)adhesion kinetics of endothelial cells are modulated by substrate stiffness and rely on the actomyosin network. We combined this approach with measurements of cell stiffness by magnetic tweezers to show that relaxation dynamics can be considered as a reliable parameter of cellular pre-stress in adherent cells. During the adhesion stage, large cellular and nuclear deformations occur over a long time span (>60 min). Conversely, nuclear deformation and condensed chromatin are relaxed in a few seconds after detachment. Finally, our results show that accumulation of farnesylated prelamin leads to modifications of the nuclear viscoelastic properties, as reflected by increased nuclear relaxation times. Our method offers an original and non-intrusive way of simultaneously gauging cellular and nuclear mechanics, which can be extended to high-throughput screens of pathological conditions and potential countermeasures.